Odpowiedzi

2010-04-08T14:45:07+02:00

c) 10=4-2x
2x=4-10
2x=-6 /:2
x=-3
d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 /:-2
x=-1,5
e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7 /:-1
t=-7
g) -(4+x)=2(3-x)
-4x-x=6-2x
-4x-x+2x=6
-3x=6 /:-3
x=-2
h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
i) (x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
- 5x=20 /:-5
x=-4
10 4 10
2010-04-08T14:49:38+02:00
C) 10=4-2x
2x=4-10
2x=-6 /:2
x=-3

d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 /:-2
x=-1,5

e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7 /:-1
t=-6

g) -(4+x)=2(3-x)
-4x-x=6-2x
-4x-x+2x=6
-3x=6 /:-3
x=-2

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

i) (x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
- 5x=20 /:-5
x=-4
3 4 3